Diagnosis of chronic thromboembolic pulmonary hypertension after acute pulmonary embolism: data from a practice-based longitudinal cohort - Hobohm, Lukas; Paschke, Lena Marie; Farmakis, Ioannis T.; Barco, Stefano; Partovi, Sasan; Münzel, Thomas; Konstantinides, Stavros; Keller, Karsten; Below, Maike (Journal of thrombosis and haemostasis, 2024)
Background - A large prospective multicenter cohort study with systematic follow-up recently reported a 2.3% 2-year cumulative incidence of chronic thromboembolic pulmonary hypertension (CTEPH) after acute pulmonary embolism (PE). - Objectives - The present investigation aimed to determine the reported prevalence and incidence of CTEPH diagnosis after acute PE in real-world practice over a 12-year period. - Methods - This study was based on nationwide ambulatory billing claims and drug prescription data of all residents with public health insurance in Germany from 2010 to 2021. - Results - A total of 573 972 patients with acute PE (median age, 71 years; 57.4% women) were identified between 2010 and 2021. Prevalence of CTEPH among patients with history of PE increased during the period from 0.4% in 2010 to 0.9% in 2021. CTEPH was diagnosed in 2556 patients after acute PE, with most (17.6%) diagnoses reported within the first 3 months after the index PE event. The cumulative incidence rate after 3 months (first quarter) was calculated at 0.08% and after the first 2 years (eighth quarter) at 0.36%; it was 0.75% over the entire (90-month) follow-up period. Patients with CTEPH diagnosis during follow-up more often had right ventricular dysfunction at the index acute PE (14.9% vs 8.3%; P < .001). - Conclusion - The low CTEPH incidence rate after acute PE in the present analysis suggests low awareness of CTEPH. It further suggests a lack of systematic follow-up protocols for acute PE survivors in the real world. Improved implementation of existing recommendations on follow-up strategies after PE is warranted.
Gesehen am 14.02.2025